Developing genetic tools to exploit Chaetomium thermophilum for biochemical analyses of eukaryotic macromolecular assemblies - Kellner, Nikola; Schwarz, Johannes; Sturm, Miriam; Fernandez-Martinez, Javier; Griesel, Sabine; Zhang, Wenzhu; Chait, Brian T.; Rout, Michael P.; Kück, Ulrich; Hurt, Ed (Scientific reports, 2016)
We describe a method to genetically manipulate Chaetomium thermophilum, a eukaryotic thermophile, along with various biochemical applications. The transformation method depends on a thermostable endogenous selection marker operating at high temperatures combined with chromosomal integration of target genes. Our technique allows exploiting eukaryotic thermophiles as source for purifying thermostable native macromolecular complexes with an emphasis on the nuclear pore complex, holding great potential for applications in basic science and biotechnology.